Role of etelcalcetide in the management of secondary hyperparathyroidism in hemodialysis patients: a review on current data and place in therapy - Friedl C; Zitt E (Dove Medical Press, 2018)
Claudia Friedl,1 Emanuel Zitt2 1Department of Internal Medicine, Clinical Division of Nephrology, Medical University of Graz, Graz, 2Department of Internal Medicine III, Nephrology and Dialysis, Feldkirch Academic Teaching Hospital, Feldkirch, Austria Abstract: Secondary hyperparathyroidism (sHPT) is a frequently occurring severe complication of advanced kidney disease. Its clinical consequences include extraskeletal vascular and valvular calcifications, changes in bone metabolism resulting in renal osteodystrophy, and an increased risk of cardiovascular morbidity and mortality. Calcimimetics are a cornerstone of parathyroid hormone (PTH)-lowering therapy, as confirmed by the recently updated 2017 Kidney Disease: Improving Global Outcomes chronic kidney disease – mineral and bone disorder clinical practice guidelines. Contrary to calcitriol or other vitamin D-receptor activators, calcimimetics reduce PTH without increasing serum-calcium, phosphorus, or FGF23 levels. Etelcalcetide is a new second-generation calcimimetic that has been approved for the treatment of sHPT in adult hemodialysis patients. Whereas the first-generation calcimimetic cinacalcet is taken orally once daily, etelcalcetide is given intravenously thrice weekly at the end of the hemodialysis session. Apart from improving drug adherence, etelcalcetide has proven to be more effective in lowering PTH when compared to cinacalcet, with an acceptable and comparable safety profile. The hope for better gastrointestinal tolerance with intravenous administration did not come true, as etelcalcetide did not significantly mitigate the adverse gastrointestinal effects associated with cinacalcet. Enhanced adherence and strong reductions in PTH, phosphorus, and FGF23 could set the stage for a future large randomized controlled trial to demonstrate that improved biochemical control of mineral metabolism with etelcalcetide in hemodialysis patients translates into cardiovascular and survival benefits and better health-related quality of life. Keywords: calcimimetic, chronic kidney disease, dialysis, etelcalcetide, secondary hyperparathyroidism